See-saw Nystagmus in Chiari Malformation Type I - Suleha, Siti; -, Yunita; Umar, Batari Todja (PT. Kalbe Farma Tbk., 2015)
Purpose: To report a case of 25 year-old woman with see-saw nystagmus as a manifestation of Chiari Malformation Type I. Methods: A 25 year-old woman was referred with involuntary movements of both eyes. Assessments were for visual acuity and anterior and posterior segments of the eyes, and magnetic resonance imaging of head and brainstem. Result: See-saw nystagmus was evident. Best corrected visual acuity were 6/6 in both eyes. Anterior and posterior segments of the eye were normal. The diagnosis of Chiari Malformation Type I was confirmed by magnetic resonance imaging. Conclusion: See-saw nystagmus can be found in Chiari Malformation Type I. No specific treatment was given.Tujuan: Melaporkan kasus seorang wanita berusia 25 tahun dengan see-saw nystagmus sebagai manifestasi Malformasi Chiari tipe I. Metode: Seorang wanita berusia 25 tahun dirujuk dengan gerakan involunter pada kedua bola mata. Pemeriksaan antara lain visus dan pemeriksaan segmen anterior dan posterior pada kedua mata serta pemeriksaan magnetic resonance imaging kepala dan batang otak. Hasil: See-saw nystagmus dapat dilihat jelas. Visus kedua mata telah dikoreksi menjadi 6/6. Segmen anterior dan posterior kedua mata normal. Diagnosis Malformasi Chiari tipe I dikonfirmasi dengan pemeriksaan magnetic resonance imaging. Simpulan: See saw nystagmus dapat ditemukan pada Malformasi Chiari tipe I. Tidak diberi terapi spesifik.